2019
DOI: 10.3389/fnbot.2019.00091
|View full text |Cite
|
Sign up to set email alerts
|

On Alternative Uses of Structural Compliance for the Development of Adaptive Robot Grippers and Hands

Abstract: Adaptive robot hands are typically created by introducing structural compliance either in their joints (e.g., implementation of flexures joints) or in their finger-pads. In this paper, we present a series of alternative uses of structural compliance for the development of simple, adaptive, compliant and/or under-actuated robot grippers and hands that can efficiently and robustly execute a variety of grasping and dexterous, in-hand manipulation tasks. The proposed designs utilize only one actuator per finger to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…For certain objects to be grasped, the grasping mode and grasp contact points should be carefully selected. It is also possible to increase the grasping stability by adding an appropriate compliant structure to the fingertip because the compliance increases the ability of a gripper to conform to the shape of the object being grasped, and also increases the area of the contact patches, increasing the grasp wrench space [37]. From Figures 21 and 22, it can be found that the static equilibrium might be difficult to achieve by using only two grasping forces, especially in the case that the two fingertips are not parallel to each other.…”
Section: Discussionmentioning
confidence: 99%
“…For certain objects to be grasped, the grasping mode and grasp contact points should be carefully selected. It is also possible to increase the grasping stability by adding an appropriate compliant structure to the fingertip because the compliance increases the ability of a gripper to conform to the shape of the object being grasped, and also increases the area of the contact patches, increasing the grasp wrench space [37]. From Figures 21 and 22, it can be found that the static equilibrium might be difficult to achieve by using only two grasping forces, especially in the case that the two fingertips are not parallel to each other.…”
Section: Discussionmentioning
confidence: 99%
“…A locking mechanism is created using a solenoid valve that allows the fingers to be locked perpendicularly to the base thereby converting the gripper to act as a parallel jaw gripper. This allows the gripper to exert higher grasping forces owing to the lack of post-contact reconfiguration in parallel jaw grippers [26]. When this mechanism is not activated, the finger has a bigger aperture for caging objects more easily, like adaptive grippers [25].…”
Section: Designmentioning
confidence: 99%
“…The sensor concept is illustrated in Figure , with panel (a) showing the IDE with compressible foam on one side, and panel (b) showing a double configuration with foam on both sides of the electrode. In panels (c) and (d), the sensor is mounted on a rigid gripping mechanism developed by Chang et al., [ 1 ] and shows how the soft sensors conform around the target object (here a kiwi fruit), thus providing information on the applied normal force without damaging the fruit. The compliance of the sensor ensures that the closing motion of the gripper only creates a gradual increase of the grabbing pressure on the target object.…”
Section: Figurementioning
confidence: 99%